The impact of technological change in rice production on food consumption and nutrition - Pinstrup-Andersen, Per; Jaramillo, Mauricio (International Food Policy Research Institute, 1991)
Technological change, such as the replacement of traditional with modern crop varieties and introduction of irrigation, has been effective in increasing the yields and production of various crops— notably rice and wheat—as well as incomes of farmers in developing countries (Pinstrup-Andersen 1982; Pinstrup-Andersen and Hazell 1985; Lipton 1989). However, the impact on food consumption and nutrition is poorly documented.